Water Quality Study to Improve Technology and Sustainability of Farmer’s Pond in Banjarpanji Village Sidoarjo - Heryono, Firman; Siswanto, Siswanto; Wijaya, Kemal (Kadiri University - Faculty of Agriculture, 2024)
The technology used in pond processing in Banjar Panji village is still traditional, with minimal labor involvement. This extensive or traditional pond does not utilize windmills, and the feed is natural. The purpose of the study was to study the physicochemical parameters of water quality in fish farming based on the Ministerial Regulation of the Ministry of Marine Affairs and Fisheries No. 75/Permen-KP/2016. The study was conducted in Banjarpanji Village, Tanggulangin District, Sidoarjo Regency, East Java. The study began from January to February 2024. Meanwhile, water sample analysis activities were conducted at the Land Resources Laboratory I and II, Faculty of Agriculture, National Development University